Bridging Language and Music: Examining the Translation Strategies in the Indonesian Subtitles of The Greatest Showman’s (2017) Song Lyrics - Fadhila Putisari Awaloedin (Universitas Sebelas Maret, 2026)
This study examines the translation strategies used in the Indonesian subtitles of song lyrics in the musical film The Greatest Showman (2017). Unlike translations intended for singing, subtitles prioritize readability and comprehension, requiring adjustments to meaning, structure, and cultural references. The research explores how the official Indonesian subtitles adapt the lyrics while maintaining coherence and accessibility for local audiences. Through a qualitative content analysis of selected lyrics, the study identifies dominant translation strategies using Gottlieb’s (1992) subtitling framework and Vermeer’s Skopos theory (1978). Findings reveal that only seven strategies are used in the Disney+ version, with transfer as the most dominant. Overall, the subtitles fulfill their communicative function, aligning with Skopos theory by preserving purpose, coherence, and fidelity within the target culture. This research contributes to audiovisual translation studies by highlighting the challenges of translating non-singable song subtitles and the importance of strategic choices in producing functional and culturally appropriate translations.